Strategi komunikasi public relations dalam meningkatkan kepercayaan nasabah pada layanan perbankan: Tinjauan literatur - M., Anggun Milania Vio (Maliki Interdisciplinary Journal, 2024)
Customer trust is a key element in the banking industry that plays an important role in the success of financial institutions. The role of Public Relations is crucial in building this trust through effective, transparent, and responsive communication with customers. This research aims to analyze Public Relations communication strategies in increasing customer trust in banking services, especially in the midst of the development of the digital era. Using the literature study method, this research examines various strategies such as the use of social media, crisis management, and the implementation of Corporate Social Responsibility (CSR) programs. The results showed that proactive, transparent, and timely public relations strategies significantly contributed to increasing customer trust and loyalty. In addition, professional handling of complaints also strengthens long-term relationships between banks and customers. This research provides important insights for the development of more effective Public Relations practices in the banking industry.